Insertion Sequence ISEcp1B Is Involved in Expression and Mobilization of a bla(CTX-M) β-Lactamase Gene - Poirel, Laurent (American Society for Microbiology, 2003)
The genetic structures (ca. 10-kb DNA fragment) surrounding the plasmid-borne extended-spectrum β-lactamase bla(CTX-M-19) gene in a Klebsiella pneumoniae clinical isolate were determined. This β-lactamase gene was part of a 4,797-bp transposon inserted inside orf1 of Tn1721. Inside this transposon, bla(CTX-M-19) was bracketed upstream and downstream by insertion sequences ISE cp1B and IS903D, respectively, and further downstream by a truncated gene encoding an outer membrane protein for iron transport. The single-copy ISEcp1B element was probably involved alone in the mobilization process that led to a 5-bp duplication at the target site of the transposed fragment. This mobilization event probably involved one inverted repeat of ISE cp1B and a second sequence farther away, resembling its second inverted repeat. Additionally, ISEcp1B provided −35 and −10 promoter sequences, contributing to the high-level expression of the bla(CTX-M-19) gene. Southern blot analysis failed to identify a reservoir of ISEcp1-like sequences among a series of gram-negative and gram-positive bacterial species usually found in the skin and intestinal human floras. The ability of ISEcp1-like elements to mobilize and to promote the expression of β-lactamase genes may explain, in part, the current spread of CTX-M-type enzymes worldwide.